Prevention of infestation by Dermestes maculatus Degeer in east African dried fish using pyrethrum and piperonyl butoxide - D., Gjerstad (Fishery Technology, 2021)
East African sun-dried fish dipped for 4 seconds in different solutions of pyrethrurn and piperonyl butoxide were analysed for insecticide residue limits. All analyses showed residues above the F AO/WHO MRL; exceeding factors of between 7.6 (22.9 ppm) and 1.6 (5.3 ppm) were found for pyrethrumwhile exceeding factors between 5.1 (102 ppm) and 1.7 (33.1 ppm) were common for piperonyl butoxide after 6 months' storage at ambient temperature. AH insecticide treated fish, regardless of dip concentration, were observed to be less susceptible to infestation by Dermestes maculatus than samples of untreated fish. No dry weight losses due to insect infestation were recorded, however moisture evaporation caused weight losses between 6 and 8 % dming the period. Further investigations showed that careful handling and a dip concentration more in accordance with F AO/WHO MRL than the commercial practice will reduce the cost of insecticides from K.sh. 0. 72 to K.sh. 0.23 per kg pyrethrum treated fish.